RELATIONSHIP OF ELEMENTS OF MATHEMATICAL ANALYSIS WITH CERTAIN PROBLEMS OF MATHEMATICS (Web of Technology: Multidimensional Research Journal, 2024)
This article contains important recommendations for the development of mathematics education and for effectively conveying the concepts of differential calculus to students and strengthening their mathematical skills. It is emphasized that teachers should teach students new, effective problem-solving methods in and out of class. The article presents the main theorems of differential calculus and examples explaining how they are used in solving mathematical problems. This process develops students' independent thinking, the desire to find new ways to solve practical problems. In addition, effective methods of using the interval method in solving inequalities help to deepen students' mathematical understanding. Also, in the article, issues related to the derivative and its practical application are shown through examples, and the importance of teaching students’ practical skills for the correct application of formulas and successful completion of mathematical mental work. is emphasized.